Single surgeon series of myelomeningocoele repairs: factors influencing outcomes - Profyris, Christos (My University, 2018)
This study reports on 24 Myelomeningocoeles (MMC) repaired at Chris Hani Baragwanath Hospital by a single surgeon. Mean gestation was 38.13 weeks, most MMCs were in the lumbosacral region and mean MMC surface area was 19.4cm2. Cerebrospinal Fluid (CSF) leak at birth was present in 50%, lower-limb neurology in 71%, lower cranial nerve dysfunction in 13% and hydrocephalus in 54%. Clubfoot was present in 71%, congenital hip dysplasia in 24%, neurogenic bladder in 82% and cutaneous abnormalities in 12%. Mean time from birth to MMC repair was 13.6 days, 46% of infants had ventriculoperitoneal shunt insertion and latex allergy was absent. Complication wise, wound dehiscence arose in 21%, CSF leak in 12.5% and infection in 25%. Neonates with CSF leak subsequently developed both wound dehiscence and CSF infection. Maternal HIV prevalence within the series was 28% and there was potential correlation between CSF infection and birth to a positive mother.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine in Neurosurgery. Johannesburg, 2018.
Keywords: Myelomeningocoeles